PEMBAHARUAN HUKUM ISLAM DI INDONESIA DAN TOKOH-TOKOHNYA - Zulhamdi Zulhamdi (Islam Futura, 2019)
The emergence of new problems or problems in the community that really need legal clarity, all of which have not been answered in either the Qur'an or the Hadith, in connection with the cessation of revelation and the death of the Prophet Muhammad who acted as a mediator between revelation and the reality that lived at that time. The renewal of Islamic law is the solution, the purpose of this paper is to find out the concepts of Islamic law reform and figures who contribute to the renewal of Islamic law. The type of research is descriptive qualitative with library research, namely research that is directed and focused on the study and discussion of library materials that have to do with the problem being studied, Overall, the renewal of Islamic law in Indonesia runs rather slowly compared to other Muslim countries, especially in the Middle East, North Africa, India and Pakistan. However, the realization of the marriage law number 1 of 1974, government regulation number 9 in 1975, Government regulation number 10 of 1983, government regulation number 28 of 1977 concerning the ownership of land, and the realization of the compilation of Indonesian Islamic law in 1991 were the dynamics of renewal of Islamic legal thinking that must be grateful, as for the characters and the ideas are: 1) Hasbi Ash-Shiddieqy (Indonesian Jurisprudence); 2) Hazairin: Indonesian National School; 3) Munawir Syadzali: Reactualization of Islamic Law; 4) Ibrahim Hosen: Making Nash Qat'i fun; 5) Ali Yafie and Sahal Mahfuz: Social Jurisprudence.